The effects of xylanase on grower pig performance, concentrations of volatile fatty acids and peptide YY in portal and peripheral blood. (6th March 2018) - Taylor, A. E.; Bedford, M. R.; Miller, H. M.
Abstract : Non-starch polysaccharides (NSP) present in wheat and barley can act as anti-nutrients leading to an increase in digesta viscosity and a reduction in nutrient digestibility. Xylanase, an NSP-degrading enzyme, has been shown to increase nutrient digestibility in pigs. The objectives of this study were: (1) to identify the optimum inclusion level of xylanase in grower pig diets by measuring the effect of increasing enzyme levels on growth performance, the concentration of volatile fatty acids (VFA) and peptide YY concentration in portal and peripheral blood of grower pigs and (2) to increase our understanding of the interrelationships between xylanase inclusion, VFA production and peptide YY secretion. A total of 512 grower pigs ((Large White×Landrace)×MAXGRO) were allocated to pens creating 32 replicates of four pigs per pen per treatment. Pigs were allocated to trial weighing 14.2±0.31 kg and remained on trial until 41.5±3.31 kg. The experiment was a dose response design with four inclusion levels (0, 8000, 16 000 or 32 000 BXU/kg) of xylanase (Econase XT). Diets were cereal-based wheat, barley mix formulated to meet or exceed the nutrient requirements of grower pigs. Body weight and feed intake were recorded to calculate growth performance. Pen faecal samples were collected to estimate DM, organic matter (OM) and crude fibre (CF) apparent total-tract digestibility. At the end of the trial 16 pigs per treatment were euthanised by schedule 1 procedures. Peripheral and portal blood samples were collected for peptide YY and VFA analysis. The addition of xylanase to the diet had no effect on growth performance, DM, OM or CF total-tract digestibility; however, xylanase tended to have a quadratic effect on ileum pH with higher pH values recorded for pigs fed a diet supplemented with 8000 and 16 000 BXU/kg xylanase ( P <0.1). Xylanase had no effect on peptide YY levels or VFA concentration. Total VFA concentration was higher in portal compared with peripheral blood ( P <0.05). In conclusion, the addition of xylanase had no effect on grower pig performance, nutrient digestibility, VFA concentration or peptide YY concentration when fed up to 32 000 BXU/kg over a 35-day period. Pig performance was good for all treatments throughout the trial suggesting that diet quality was sufficient thus there were no beneficial effects of adding xylanase.